Two interesting cases of gestational trophoblastic disease with methotrexate failure - Laul, Poonam; Saxena, Pinkee; Kadam, Vijay K.; Miglani, Urvashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Gestational trophoblastic disease is group tumours that are more sensitive and respond well to a wide variety of chemotherapeutic regimes. Presented here are two interesting cases one with life threatening bleeding requiring hysterectomy and other with persistent disease post evacuation. Both being low risk were treated with single agent methotrexate, but failed to respond. They responded to alternative chemotherapy. Methotrexate resistant is seen even in low risk group.